The risks and benefits of internal monitors in laboring patients - Harper, Lorie M.; Shanks, Anthony L.; Tuuli, Methodius G.; Roehl, Kimberly A.; Cahill, Alison G. (American journal of obstetrics and gynecology, 2013)
The purpose of this study was to estimate the impact of internal monitors (fetal scalp electrode [FSE] and intrauterine pressure catheter [IUPC]) on maternal and neonatal outcomes. The study comprised a retrospective cohort of all women who were admitted for labor from 2004-2008. Women with internal monitors (FSE, IUPC, or both) were compared with women without internal monitors. Maternal outcomes were maternal fever and cesarean delivery. Neonatal outcomes were a composite of 5-minute Apgar score of ≤3, cord pH <7.1, cord base excess ≤−12, or admission to level 3 nursery. Logistic regression was performed to estimate the impact of internal monitors with adjustment for confounding variables, including time in labor. Of 6445 subjects, 3944 women (61.2%) had internal monitors. Women with internal monitors were more likely to have a fever than women without internal monitors (11.7% vs 4.5%; adjusted odds ratio [AOR], 2.0; 95% confidence interval [CI], 1.6–2.5). FSE alone was not associated with an increased risk of fever (AOR, 1.5; 95% CI, 1.0–2.1), but IUPC alone was (AOR, 2.4; 95% CI, 1.8–3.2). The risk of cesarean delivery was higher in women with internal monitors (18.6% vs 9.7%; AOR, 1.3; 95% CI, 1.0–1.5). Risk of cesarean delivery was lower in women with an FSE alone (AOR, 0.5; 95% CI, 0.4–0.7) but higher in women with both an FSE and an IUPC (AOR, 1.6; 95% CI, 1.4–2.0). Risk of the composite neonatal outcome was not higher in women with internal monitors (3.3% vs 3.6%; AOR, 0.8; 95% CI, 0.6–1.1). Routine use of an IUPC in laboring patients should be avoided because of an increased risk of maternal fever.